Knee extensor morphology and sprint performance in preadolescent sprinters - Tottori, N.; Suga, T.; Isaka, T.; Fujita, S. (Research Quarterly for Exercise and Sport, 2022)
Purpose: We previously reported that the cross-sectional area of the quadriceps femoris is correlated with the sprint performance of preadolescent sprinters. This finding suggests a close relationship between knee extensor torque-enhancing morphology and sprint performance in this young population. To further clarify this issue, in this study, we examined the relationships of the quadriceps femoris muscle volume (MV) and knee extensor moment arm (MA) with sprint performance in preadolescent sprinters.